Developmental dysplasia of the hip: a history of innovation. Issue 3 (May 2018) - Tarpada, Sandip P.; Girdler, Steven J.; Morris, Matthew T.
Abstract : Developmental dysplasia of the hip (DDH) is a relatively common malady that has profound consequences in the infant if left untreated. Effective and early treatment of DDH has been praised as one of the most successful ventures of modern pediatric orthopedics. Yet, before the modern management of DDH came into existence, there were extensive technological developments in the field of harnesses, casts, and traction methods. This paper aims to identify the centuries-old history of advancement in DDH treatment and the many important people involved. Their devices, thoughts, and ideas continue to have a profound impact on the current practice of orthopedic surgery.